PREDICTIVE FACTORS AFFECTING THE MATHEMATICS PERFORMANCE OF K-12 GRADUATES: Attitude towards Mathematics, Mathematics Performance, Predictive Factors, Profile and K-12 Graduates - TAMAYO, SHIALLY (International Journal of Arts, Sciences and Education, 2021)
This study determined the predictive factors affecting the performance of the K-12 graduates in Mathematics. It identified the profile, mathematics performance and attitude of the respondents. Furthermore, it determined the difference on the academic performance of the respondents in mathematics when grouped according to profile and it studied which among the independent variables best predict the performance of the respondents. The study used the descriptive design. The survey-questionnaire was used to gather data and the data were analyzed using the frequency counts, mean, percentage, multiple Regression, T-test and ANOVA. The study found out that majority of the respondents are early adults, females and General Academic Strand (GAS) graduates. The respondents’ fathers are high school graduates; while, their mothers are college graduates with family income that range from 2,100-5,000. The mathematics performance of the respondents is “good”. The study found out that there is no significant difference on the Mathematics performance of the respondents when grouped according to age, sex, highest educational attainment and monthly income of the respondents’ parents. In contrast, the study found out that the Senior High school track was significantly related to the academic performance of the respondents. And the findings revealed that among the variables, Mathematics attitude best predict Mathematics performance.